(untitled) (Altre Modernità, 2009)
The article deals with the increase of a population of immigrant origins’ youth in Italy, starting from a piece of research, conducted by different methods: 1- a survey on families whose members have been separated during the migration and now they are rejoined 2- a survey on pre-adolescents (11-14 years old) 3- a survey on educational outcomes in secondary school 4- a survey on the opinion of immigrant origins’ youth about citizenship The scenario outlined, where a youth population of foreign origins becomes more an more visible, questions the social and political institutions, and compels to rethink the concepts of Italian society and Italian cultural identity.